Fulminant necrotizing fasciitis secondary to Aeromonas dhakensis infection: a case report - Li, Xiaoxia; Gu, Juanxian; Zhang, Weifang; Zhang, Qinhua; Fang, Zebin; Jin, Bin; Ou, Zhenfei; Huang, Xiao (Frontiers in Medicine, 2025)
BackgroundNecrotizing fasciitis (NF) is a kind of rapidly destructive soft tissue infection with an unfavorable prognosis. It is usually caused by highly virulent bacteria. Recently, the incidence of NF caused by atypical opportunistic pathogens has been increasing. Aeromonas dhakensis is increasingly emerging as a new, highly virulent, biofilm-producing, and multidrug resistant cause of soft tissue infection. The current strains of A. dhakensis are causing increasingly severe disease, with delayed diagnosis and treatment.Case presentationWe report a rare case of NF caused by A. dhakensis in a 47-year-old man with liver cirrhosis. He presented 2 days after the onset of fever and painful erythema involving his right lower limb. On admission, the patient was febrile and hypotensive with signs of septic shock and necrotizing soft tissue infection. Blood cultures were rapidly positive for A. dhakensis. Multiple imaging studies demonstrated diffuse involvement of the soft tissues, and the patient developed multiple organ dysfunction syndrome (MODS). Despite early-onset broad-spectrum antimicrobial therapy, emergency surgical debridement, and organ support, the patient’s condition continued to decline. Given the extremely poor prognosis, the family decided against further treatment and discharged the patient from the hospital.ConclusionThis case underscores the necessity of not overlooking opportunistic and atypical pathogens, such as Aeromonas dhakensis, especially in high-risk susceptible populations, in rapidly progressing soft tissue infections. Early empirical and targeted antimicrobial therapy, prompt surgical intervention, integrated critical care management, and rigorous public water safety measures are all pivotal to improving patient outcomes and preventing similar adverse events.